Digital Transformation in HR Management: The Role of Human Resource Analytics in Decision-Making Effectiveness - Maulid Sakaria (Maneggio, 2025)
ABSTRACT This study aims to analyze the influence of Digital Transformation and Human Resource Analytics on Decision-Making Effectiveness in the context of human resource management. This study uses a quantitative approach with a survey method, involving 150 respondents consisting of HR employees, leaders, and managerial staff in public and private organizational sectors. Data collection was carried out through a five-point Likert scale questionnaire that has been tested for validity and reliability. Data analysis used multiple linear regression with the help of SPSS software version 26. The results of the study indicate that: (1) Digital Transformation has a positive and significant effect on decision-making effectiveness (significance value 0.000 < 0.05); (2) Human Resource Analytics also has a positive and significant effect on decision-making effectiveness (significance value 0.001 < 0.05); and (3) simultaneously, the two independent variables contribute 71.2% to increasing decision-making effectiveness. These findings confirm that the integration of digital technology with HR data analysis plays a crucial role in creating faster, more accurate, and evidence-based decision-making. This research provides theoretical implications for the development of the Data-Driven HR concept, as well as practical recommendations for organizations to strengthen digital and analytical capabilities within their HR management functions. It is hoped that future research will incorporate a mixed methods approach to explore the contextual and cultural aspects that influence decision effectiveness in the digital age.